Influence of sprayed nanocrystalline Zn-doped TiO2 photoelectrode with the dye extracted from Hibiscus Surattensis as sensitizer in dye-sensitized solar cell. Issue 9 (July 2016) - Arunachalam, A.; Dhanapandian, S.; Manoharan, C.; Bououdina, M.; Ramalingam, G.; Rajasekaran, M.; Radhakrishnan, M.; Ibraheem, A. Mohamed
Abstract: Highly oriented Zn doped TiO2 thin films (0, 2, 4, 6 and 8 at%) were deposited by spray pyrolysis technique. X-ray diffraction analysis showed a strong orientation along (101) direction for 6 at% Zn with polycrystalline tetragonal anatase phase. Scanning electron microscopy observations revealed uniform distribution of spherical-shaped grains, whereas columnar arrangement of tetragonal-shaped grains with porous nature was revealed from atomic force microscopy. Transmittance spectra indicated a decrease in the energy band gap with increasing doping concentration; i.e. 3.55 up to 3.21 eV, attributed to grain refinement to the nanoscale regime. The optical constants such as refractive index and extinction coefficient as a function of wavelength, were determined; the low extinction coefficient values confirmed the good quality of the thin films. Photoluminescence spectra showed strong emissions at 423 and 437 nm with a weak emission at 505 nm, which confirmed the lesser defect density in 6 at% Zn film. The electrical properties studied by Hall Effect measurements revealed that the 6 at% Zn led to an increase in the carrier concentration, as well as an increase in the mobility with a least resistivity. The efficiency of dye sensitized solar cells, assembled by using natural dye extracted from Hibiscus Surattensis as sensitizer and Zn-doped TiO2 nanocrystalline thin films as a photoelectrode, was found to be around 1.22%. Graphical abstract: